Ethics and law for social workers - Johns, Robert 1950- (Los Angeles SAGE, 2016)
"How do social workers in the UK legal context act ethically? What do we understand by ethics and how does social work law relate to it? Social work practice in all countries incorporates a clear, unstinting commitment to social justice, but what is social justice? Using an applied, practice-based and refreshingly 'real' approach, this text bridges the gap between law and ethics. Each chapter open with a case study which considers ethical dilemmas in real life practice. Chapters have been designed to help students strengthen their critical reflection skills, encouraging consideration of the legal and ethical dimensions of social work generally and in personal practice. Through an examination of topics such as care proceedings, adoption, community care, youth justice, mental capacity and accountability the book demonstrates how understanding both ethical theory and its application to practice are equally important"--Back cover.
Introduction: but I want to be a social worker, not a philosopher! -- Judging actions or people? -- Social workers, social justice and the law -- Accountability, ethics and the law -- Protecting children or supporting parents? -- Whose future? The ethics of compulsory adoption law -- Youth justice -- Community care and the ethics of resource allocation -- Making decisions on behalf of other people: promoting the best interests of vulnerable adults -- Acting legally, acting ethically.
Includes bibliographical references (pages 177-182) and index.
Keywords: Social workers -- Legal status, laws, etc. -- Great Britain; Social service -- Moral and ethical aspects -- Great Britain; Public welfare -- Law and legislation -- Great Britain